2009
DOI: 10.1007/s12194-008-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

Need for liquid–crystal display monitors having the capability of rendering higher than 8 bits in display-bit depth

Abstract: Our purpose in this study was to examine the potential usefulness of liquid-crystal display (LCD) monitors having the capability of rendering higher than 8 bits in display-bit depth. An LCD monitor having the capability of rendering 8, 10, and 12 bits was used. It was calibrated to the grayscale standard display function with a maximum luminance of 450 cd/m(2) and a minimum of 0.75 cd/m(2). For examining the grayscale resolution reported by ten observers, various simple test patterns having two different combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It may be reasonable to assume that medical-grade displays offer an advantage when radiologists need to identify low-contrast objects, which requires maximal display performance (3,20). Another study directly addressed this issue by investigating the presence or absence of subtle low-contrast bone fissures on medical-graded versus calibrated consumer-grade displays and also reported no significant difference, concluding that calibrated consumer-grade displays may be sufficient for most radiological examinations (3).…”
Section: Discussionmentioning
confidence: 99%
“…It may be reasonable to assume that medical-grade displays offer an advantage when radiologists need to identify low-contrast objects, which requires maximal display performance (3,20). Another study directly addressed this issue by investigating the presence or absence of subtle low-contrast bone fissures on medical-graded versus calibrated consumer-grade displays and also reported no significant difference, concluding that calibrated consumer-grade displays may be sufficient for most radiological examinations (3).…”
Section: Discussionmentioning
confidence: 99%
“…Medical-grade displays can be expected to provide an advantage when radiologists need to detect low-contrast objects, which requires maximum display performance [ 2 , 21 , 22 , 23 ]. Most studies published to date provide only quantitative accuracy data, while we also tried to include subjective impressions of our readers, which they rated on Likert scales.…”
Section: Discussionmentioning
confidence: 99%
“…19 It also highlights the fact that the high luminance monitors that are now available for clinical applications in dentistry as well as COTS monitors that are also used for this purpose should make the best use of the JNDs within their range, and this can be achieved by calibrating them to the DICOM part 14: GSDF. 2 In an interesting investigation by Hiwasa et al, 20 where the greyscale resolution of monitors was investigated by displaying simple test patterns having various grey levels in 8, 10 and 12 bits on a DICOM part 14: GSDF-calibrated LCD monitor, they found that the observers were able to distinguish more grey levels as the bit depth was increased. However, Bender et al 21 found that even though the higher greyscale resolution results in a more complete visualization of image information, radiologists partially judged this as a lack of sharpness and contrast and generally preferred the 8-bit display.…”
Section: Discussionmentioning
confidence: 99%